#### Answer

$F(\frac{3\pi}{2})=\frac{1}{2}$
This means that the half of the moon's face is illuminated by the sun.

#### Work Step by Step

$F(t)=\frac{1}{2}(1-\cos t)$
For $F(\frac{3\pi}{2})$, the phase angle $t=\frac{3\pi}{2}$. Substituting $t=\frac{3\pi}{2}$ in the equation,
$F(\frac{3\pi}{2})=\frac{1}{2}(1-\cos \frac{3\pi}{2})$
$F(\frac{3\pi}{2})=\frac{1}{2}(1-(0))$
$F(\frac{3\pi}{2})=\frac{1}{2}(1)$
$F(\frac{3\pi}{2})=\frac{1}{2}$
This means that the half of the moon's face is illuminated by the sun.